Thai Religion and the Viability of the Construct ‘Cult’ - Kosuta, Matthew (Poligrafi, 2022)
This article takes the construct of ‘cult’ as used in academic work, defined in part as a ‘social formation’, and applies it to Thai religion in order to assess its viability as a descriptive and/or analytical category in the Thai religious context while highlighting elements of Thai religious belief and practice to identify possible cognate words to ‘cult’ in the Thai language (wai (pay respect), būchā (sacrifice, worship), būang sūang (worship, appease), etc.). The article presents an overview of the use of cult, or lack thereof, in current research on Thai religion (worship of Buddha, monks, kings – living and deceased, revered monks, Rahu, local deities and spirits). Reference will be made to the extensive use of ‘cult’ in studies of Greek and Roman religion. Outcomes show that in Thai religion there is rarely, if ever, formal membership in ritual practice and worship is fluid with individual Thais free to move between what can be termed ‘cults’ thus weakening the viability of the term. While one can certainly say the “cult of King Naresuan”, the fluidity of Thai religions strains the parameters of the construct of ‘cult’ as a social formation in Thailand.